Feasibility Assessment and Implementation of Integrated Management of The West Coast of The Mazandran Province According to the ICZM - Habibeh Karimi; Khatereh Bagherzadeh Asl; Samira Torabi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Integrated coastal zone management (ICZM) is the primary way to solve environmental problems. In addition, many countries in the world attempt to provide human needs to coastal region services to reach the natural border of these zones. The primary purpose of this paper is to identify the current situation of pollution in different coastal areas of Mazandaran province and the zoning of areas in terms of environmental pollution. Methodology: In this paper, we first deal with the conceptual framework of ICZM, study the successful examples of its implementation in different countries, and compare them from various aspects. Then, to implement this project on the west coast of Mazandaran province, we will pay attention to the studies related to environmental pollution. Findings: Findings show that in coastal management, all physical, ecological, social, and economic processes that interact on the coast and the sea should be identified, and specific coordination between different users at local, national, regional, and international levels must be created. Furthermore, the successful implementation of ICZM requires more attention to the social and economic conditions of the Caspian littoral states. Originality/Value: We study the characteristics of the west coast of Mazandaran province based on important ecosystems and parameters such as industrial pollutants, soil type, vegetation (sea and land), wildlife, geology, and marine topics (water fluctuations, wave characteristics, etc.) And we analyze the related issues. Finally, to implement the ICZM on the west coast of Mazandaran province, from the point of view of environmental pollution, we investigate the distribution of industrial pollutants in the use of coastal lands up to a radius of three kilometers in the Caspian Sea.